2015
DOI: 10.7554/elife.10935
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by small-molecule ligands of formation of amyloid fibrils of an immunoglobulin light chain variable domain

Abstract: Overproduction of immunoglobulin light chains leads to systemic amyloidosis, a lethal disease characterized by the formation of amyloid fibrils in patients' tissues. Excess light chains are in equilibrium between dimers and less stable monomers which can undergo irreversible aggregation to the amyloid state. The dimers therefore must disassociate into monomers prior to forming amyloid fibrils. Here we identify ligands that inhibit amyloid formation by stabilizing the Mcg light chain variable domain dimer and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 51 publications
3
41
0
Order By: Relevance
“…S9). This binding site is consistent with previous reports that the interface between V domains in the dimer can accommodate various aromatic ligands (21,42), although the exact binding site that we identify below has not been previously observed. The binding site for 1 comprises residues P44, Y87, and F98 from one protomer and Y36ʹ, P44ʹ, and T46ʹ from the other protomer ( Fig.…”
Section: -Amino-coumarins Are Fluorogenic Kinetic Stabilizers Of λ6asupporting
confidence: 92%
See 2 more Smart Citations
“…S9). This binding site is consistent with previous reports that the interface between V domains in the dimer can accommodate various aromatic ligands (21,42), although the exact binding site that we identify below has not been previously observed. The binding site for 1 comprises residues P44, Y87, and F98 from one protomer and Y36ʹ, P44ʹ, and T46ʹ from the other protomer ( Fig.…”
Section: -Amino-coumarins Are Fluorogenic Kinetic Stabilizers Of λ6asupporting
confidence: 92%
“…Edmundson et al (42) identified regions within the interface between the V domains of an amyloidogenic FL LC, known as MCG, that could bind hydrophobic ligands. Brumshtein et al (21) reported small molecules that bind to the MCG-V domain and prevent its aggregation (21). However, neither of the small molecules for which cocrystal structures were solved (sulfasalazine and methylene blue) were active in our PCFP assay employing WIL-FL* (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This model is also supported by data from a recent drug screen (66). We found that ϳ50% of LC in urine existed as disulfidecross-linked dimers, and all LC existed as di-or multimers under native conditions.…”
Section: Discussionsupporting
confidence: 80%
“…This suggests that treatment with anti-amyloid drugs that either stabilize the native LC dimer or inhibit amyloid formation may be a promising supplemental therapeutic strategy to ameliorate the amyloid pathology in AL patients. It would therefore be valuable to assess the potential of drugs, such as EGCG, methylene blue, and Orcein/ O4, which have proven effective in inhibiting amyloid formation in other disease-related proteins, for the treatment of AL amyloidosis (32,66,86).…”
Section: Discussionmentioning
confidence: 99%